Telehealth Potential to Optimize Self-Management, Education, and Support for Diabetes Mellitus Patients during COVID-19 Pandemic - Melati, Azalia; Mulyani, Santi; Agustin, Amellia; Rifa'atul Fitri, Siti Ulfah (International Journal of Nursing and Health Services (IJNHS), 2022)
Background: The limited physical interaction policy during the COVID-19 pandemic and concerns of DM patients visiting healthcare facilities cause routine visits delays, treatment discrepancies, and ineffective health education. Telehealth can provide DM patients convenience of self-management during pandemics. Objective: This review aims to discover the potential use of telehealth to optimize Self-Management, Education, and Support for DM patients during the COVID-19 pandemic. Method: Rapid review has been done by conducting a systematic search on five databases: PubMed, EBSCO-host Academic Science Completed, ScienceDirect, Sage Journals, and Taylor and Francis. The articles have been identified through the following criteria: the year of publication is at most two years old (2019-2021), the research design used is strictly Randomized Control Trial and Quasi Experiment, and the published language must be English. Results: It was found that some telehealth-based interventions, such as remote monitoring of independent blood glucose levels, education through text messaging, telephone, and Technological Surrogate Nursing (TSN), can effectively facilitate self-management of patients with diabetes. The main features mentioned are reminders, automatic data processing systems, education in the form of modules and videos, and call center services for regular follow-ups. Telehealth is an online-based health service that has the potential to optimize the self-management of DM patients.